Metaphor as a means of visualizing an object of naming in media texts (a case study of the Russian, English, Tatar and Tuvan languages) - Kiseleva, Larisa A.; Todosienko, Zarrina V.; Lukmanova, Renata R.; Kuular, Elena M. (The New Research of Tuva, 2022)
The article identifies metaphorical models that determine the principles of verbal visualization of the realities of culture and show business in media texts. It incorporates materials of multi-structural unrelated / not closely related languages (Russian, English, Tatar, Tuvan).It has been found out that these models have different potential in terms of figurative representation of the phenomenon being designated. Systemic (linguistic) metaphors hold the least potential being widely replicated and therefore devoid of the effect of novelty (Rus. звезда / zvezda; Eng. star; Tat. йолдоз / ioldoz; Tuv. сылдыс / syldys). More ample imaginative possibilities are typical for metaphorical models that reflect specific associative connections of concepts (Rus. ад / ad; Eng. bubble, cloud; Tat. өзү / ozu; Tuv. аскымнаар / askymnaar; et al.).The models are largely universal in nature, that is, they are presented in four/three languages that are analyzed (“physical action → emotional impact”, “heavenly body → human being”, etc.). In some cases, there is a parallelism of semantic structures of multilingual lexemes (Rus. рассадник / rassadnik; Eng. breeding; etc.).Unique models of metaphorization, which are based on associative relations of concepts that are difficult to explain from a logical point of view, are characteristic of only one of the languages under study, for instance: “physiological impact → intellectual/emotional impact” (in English), “movement → speech activity” (in Tuvan), etc.It is shown that most of the metaphorical images used in media texts correlate with the anthropomorphic and objective codes of culture: the inner form of the analyzed lexemes is associated either with the animation of processes, states, etc., or with their objectification. The active use of metaphorical means in media texts is partly due to the predominance of the visual principle in contemporary culture. This principle facilitates the perception of a message and deciphering its meaning.
Keywords: metaphor; semantic model; visualization; mass media; anthropocentrism; Tuvan language; Russian language; English language; Tatar language